Performance of cementitious materials produced by incorporating surface treated multiwall carbon nanotubes and silica fume - Al-Tamimi, Adil (2016)
The outstanding mechanical properties of carbon nanotubes (CNTs) highlight them as potential candidates for cementitious material reinforcement. However, their low surface friction and the Van der Waals forces of attraction between them, cause the CNTs to aggregate with each other rather than bind with the cement matrix. A number of methods have been investigated by researchers to reduce the aggregation, improve dispersion and activate the graphite surface to enhance its interfacial interaction. These methods involve surface functionalization and coating, optimal physical blending, use of surfactant and other admixtures. This research investigates the use of silica fumes (an admixture), surface functionalized CNTs and cement paste to overcome those obstacles. CNTs with polar impurities end groups OH and COOH were examined. Mortar samples with non-functionalized CNTs dispersed in water solution, another with non-dispersed, non-functionalized CNTs, and a third batch with no CNTs (as control) was used also studied. Silica fumes volume fraction was varied from 0 to 30% to determine its effect. Compressive and flexural strengths of the different mixes were measured and compared. Qualitative analysis using Scanning Electron Microscope (SEM) and Energy-Dispersive Spectroscopy (EDS) were carried out to study the morphology of each mix. Results reveal a much higher enhancement in strength both compressive and flexural strengths for the functionalized CNTs with 30% silica fumes over the other samples.